PENGEMBANGAN MODUL TUMBUHAN (PLANTAE) DENGAN MODEL PROBLEM-BASED LEARNING BERBASIS LITERASI SAINS (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstarct: This research aims to develop modules with problem-based learning (PBL) models based on science literacy on plant materials, analyze the feasibility of modules with science literacy-based PBL models, analyze modules with science literacy-based PBL models. This type of research is development research using the ADDIE model. This research is carried out until stage 3, which is the development stage. Instruments used for data collection are validation sheets, response questionnaire sheets. The trial was conducted on students of class XI SMAN 1 Pekanbaru. The results showed that modules developed with a science literacy-based PBL model were highly viable with an average score of 87.1. The analysis of the module's exposure was obtained from the results of trial I with an average score of 95.2 and trial II with an average score of 95.7 with an excellent category. This shows that the modules developed are highly viable for use and the application of modules with a science literacy-based PBL model can improve learning outcomes and strengthen students' science literacy.Key Words: Module, Plantae, Problem-Based Learning, Science Literacy.